Teacher's Communication and Interaction Style: Efforts to Build Student Confidence in Fiqh Learning - Tuaini Tuaini; Syamsul Arifin; Faridi Faridi; Romelah Romelah (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The aim of this study is to explore how a teacher’s communication and interaction style affects students’ confidence in learning Fiqh. Methodology: This research employs a qualitative method with a phenomenological focus, utilizing a descriptive approach. Conducted at MAN Palangka Raya, Central Kalimantan, it involves one Fiqh teacher as the subject. Informants include the school principal, student representatives, and students from grades X selected through purposive sampling. Data validation uses source triangulation, and analysis follows steps of data collection, reduction, presentation, and conclusion drawing. Main Findings: Teacher communication positively impacts student learning achievement, independence, optimism, and self-confidence. Novelty/Originality of this study: This study reveals the specific effects of teacher communication and interaction styles on students’ self-confidence in Fiqh enhances existing knowledge by emphasizing the direct relationship between effective teacher-student interactions and improved student confidence. The findings offer practical implications for educators, suggesting ways to optimize educational environments to foster student engagement and confidence.